Memperbaiki Kemampuan Berpikir Kreatif Siswa melalui Problem Based Learning dan Creative Problem-SolvingProcessdi Pelajaran Biologi - Wiji Setyo Utami; Murni Ramli; Joko Ariyanto; Bambang Riyanto (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
Creative thinking may be nurtured by training the students in the problem-solving and steps to think creative. The main problem of students in grade X Science 5 in the current school target is students were difficult to think creatively. They commonly answered teacher’s questions in a very brief answer. To solve this problem, we combined theProblem Based Learning (PBL) and Creative Problem-Solving Process (CPSP) as an intervention in this three cycles classroom action research. Following the cycles, we checked the changes of student’s behavior by assessing student’s creative thinking skills. Each cycle followed the spiral cycle of action research introduced by Kemmis and McTaggart. In the first cycle, the original PBL and CPSP were applied, and the result was students have not be able to express original idea in detail, to determine the focus of the problem, and have not be able to evaluate performance. They have lack initiative, independence, and sensitivity to the problem too. In the second cycle, action was modified by media improvement, changes in the way of group sharing, the extent of material coverage, and presentation technique. The change of student’s abilities were students had been able to express their original idea, but not yet detailed. Students were independent and sensitive to existing problems. Some students were able to evaluate their performance too. The last cycle applied with modification in the form of material reduction, change of group members, and problem-solving questions on student’s worksheet. The result was students had been able to express their original ideas in detail, determined the focus of the problem, and evaluated their performance. Students also had initiative, independence, and sensitivity to the existing problem. Data of 32 student’s creative thinking abilities were measured through a series of test and questionnaire, which then descriptively analyzed. Overall, all students have achieved good category in creative thinking at the end of action research. It can be concluded that the PBL and CPSP is potentically improving student’s creative thinking abilities.